Geology and U-Pb geochronology of the Island Lake greenstone belt, northwestern Superior Province, Manitoba - Corfu, Fernando; Lin, Shoufa (Canadian Journal of Earth Sciences, 2000)
Mapping and U-Pb geochronology have been used to examine the tectonic and depositional history of the Archean Island Lake greenstone belt in the northwestern Superior Province. The Island Lake greenstone belt comprises two main supracrustal successions, the older Hayes River Group and the younger Island Lake Group. Zircon data for two volcanic units from the Hayes River Group provide identical ages of 2852 ± 1.5 Ma, whereas a turbidite of this group contains a detrital zircon population with ages between 2858 and 2847 Ma. Younger intrusive events include the emplacement of tonalite in the southern batholith at 2825 ± 2 Ma and the Whiteway Island gabbro at 2807 ± 1 Ma. A wacke at the base of the Island Lake Group is dominated by detrital zircon grains yielding ages between 2830 and 2821 Ma, the latter defining a maximum age of sedimentation. A relatively early time of deposition of the lower stratigraphic sections of the Island Lake Group is also supported by an age of 2744 ± 2 Ma obtained for a crosscutting tonalite. By contrast, two turbidite horizons from higher stratigraphic levels of the Island Lake Group contain detrital zircon populations with ages mostly younger than 2730 Ma, the youngest zircon grains providing maximum ages of sedimentation at 2722 and 2712 Ma, respectively. Our results confirm the protracted evolution of the greenstone belt and show in particular that major sedimentary processes were active throughout the main stages of volcanism of the belt. This pattern of protracted sedimentation is comparable to that observed in other greenstone belts of the northwestern Superior Province, all of which developed on pre-Kenoran crust.